Hemolytic Anemia In A Neonate: A Diagnostic Dilemma - Singh, Parminder; Gupta, Divya (Annals of Pathology and Laboratory Medicine, 2018)
A 5 days old male neonate was brought with icterus till forearms and legs with no other associated symptoms. He was born to a 30 year old second gravida lady with mother’s blood group being B positive and perinatal transition being uneventful. Investigations revealed unconjugated hyperbilirubinemia nearing exchange transfusion range with severe hemolytic anemia. The neonate was managed with intensive phototherapy and packed red cell transfusions. Further workup ruled out the possible known common causes of hemolytic anemia of neonate, the DCT was negative, no G6PD deficiency was present, no RBC membrane or enzyme defects. So even after an exhaustive workup of our case, the cause of hemolytic anemia still remains unexplored.